Data mining with rattle and R the art of excavating data for knowledge discovery - Williams,Graham (Springer, 2011)
Data mining is the art and science of intelligent data analysis. By building knowledge from information,data mining adds considerable value to the ever increasing stores of electronic data that abound today. In performing data mining many decisions need to be made regarding the choice of methodology, the choice of data, the choice of tools, and the choice of algorithms. Throughout this book the reader is introduced to the basic concepts and some of the more popular algorithms of data mining. With a focus on the hands-on end-to-end process for data mining, Williams guides the reader through va.